2015
DOI: 10.1108/jcp-01-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of peer network interactions on adolescent cannabis use

Abstract: Purpose: This study capitalises on three waves of longitudinal data from a cohort of 4351 secondary school pupils to examine the effects on individuals' cannabis use uptake of both peer cannabis use and position within a peer network. Methodology:Both cross-sectional and individual fixed effects models are used to estimate the effect on cannabis use of nominated friends' cannabis use, of reciprocity and transitivity of nominations across the friendship cluster, and of interactions between these nominated frien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…As we expected, our results display a positive and significant influence of P_TOLER and PEER_USE on USE. Whereas in the case of P_TOLER our results confirm those in [5,9,13,14,18,19,21,22] our findings over PEER_USE are in the line of [4,13,14,18,[25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As we expected, our results display a positive and significant influence of P_TOLER and PEER_USE on USE. Whereas in the case of P_TOLER our results confirm those in [5,9,13,14,18,19,21,22] our findings over PEER_USE are in the line of [4,13,14,18,[25][26][27][28][29][30].…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, literature reports that school engagement; academic success and influence by friends are relevant factors to explain cannabis use. In this regard, whereas [4,9,16,24] outline academic performance and engagement to school as a significant factor to explain drug consumption [4,13,14,18,[25][26][27][28][29][30] found decisive the behavior and attitude of peers toward substance use to explain cannabis consumption by teenagers.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses also indicate exposure to a parent/carer’s drinking when aged 14 is associated with offspring’s subsequent drinking from mid-adolescence, extending into early adulthood [ 31 ]. Social network analysis of cannabis use across three waves found that use varied depending on the stability of the friendship network and degree of reciprocity and interconnectedness within the group, concluding that preventing an individual from using cannabis was likely to have a multiplier effect on classmates [ 32 ]. Modelling based on the social network data also found evidence that cross-sectional data can be used to estimate peer effects on cannabis use [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…As such, teenagers who see their peers benefitting financially from illicit marijuana cultivation and trading will be compelled to do same. Moriarty and Higgins [ 56 ] further explain that behavioural influence is strong among teenagers who have stable friendship networks. Hence, adolescents from a rural community where friendship networks are more stable and stronger [ 57 ] are likely to engage in illegal marijuana cultivation if their peers were involved in such a practice.…”
Section: Discussionmentioning
confidence: 99%